MAKNA PERAYAAN EKARISTI SEBAGAI PERAYAAN KASIH BAGI KELUARGA KATOLIK DI PAROKI ST.YOSEP RUMAH TIGA - Sainyakit, Andreas; Mangar, Richardo Feilobo (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2023)
This study discusses the meaning of the Eucharistic Celebration as a Celebration of Love for a Catholic family who lives in the parish of St. Joseph Rumah Tiga. This title was taken based on the anxiety that the author experienced while attending the Eucharist celebration where many Catholics today have started not participating in the Eucharistic celebration. This may be due to a lack of understanding of the meaning of the Eucharist itself, and the author feels that all aspects of the life of the faithful are first and foremost in the family where he is educated. With the research method, the research seeks to find out how the people's understanding of the Eucharist celebration itself is and the extent of its influence on the family life of the faithful who live in the parish of St. Joseph Rumah Tiga. And after conducting a series of research in this thesis, it was found that it is not uncommon to be bored in the Eucharistic Celebration itself but this does not reduce the understanding and meaning of the faith of the Catholic family in the parish towards the importance of the Eucharist. most of the families are quite good at understanding and interpreting the Eucharistic Celebration, so that what the author experienced was not carried out by the whole family who lives in the St. Joseph Parish, Rumah Tiga. Keywords: Eucharist Celebration, Celebration of Love, Catholic Family